Effect of body size and copper exposure on physiological responses of green mussel Perna viridis (Linnaeus) - Krishnakumar, P K; Damodaran, R (Indian Journal of Fisheries, 2011)
Effect of body size on some of the physiological stress indices like oxygen consumption, ammoniaexcretion, O : N ntio, filtration rate and body condition index (BCI) were studied. Comparatively lowO : N ratio (23.09) was obtained for Perna viridis, indicating a heavy dependence on protein for energyproduction. Oxygen consumption (b=0.7014), ammonia excretion (b=0.4155), 0:N ratio (b=0.2377) andfiltration rate (b = 0.5070) were positively correlated and body condition index negatively correlated(b =- 0.2237)with the increase in body weight.In mussels exposed to 7.5 \lg litre ' of copper, for 20 days, all stress indices except O : N ratio,declined with the increase in tissue copper concentration. The tissue copper concentration increased from8.34 to 196.91 ug $-' dry tissue weight.